PERAN XIAOHONGSHU DALAM PROMOSI PARIWISATA BALI PASCA PANDEMI COVID-19 (Jurnal Destinasi Pariwisata, 2026)
The recovery of Bali’s tourism sector from the Chinese market after the COVID-19 pandemic has remained uneven despite the destination’s exceptionally high digital visibility on Chinese social media platforms. This study aims to examine how Xiaohongshu mediates destination image formation and travel decision-making among Chinese Generation Z tourists during Bali’s post-pandemic recovery phase. A qualitative single case study approach was employed, integrating systematic digital observation of Xiaohongshu content with in-depth interviews conducted in 2025 involving 17 Chinese Gen Z users and six tourism stakeholders in Bali. Data were analyzed using Applied Thematic Analysis to identify patterns in motivational dynamics and platform influence. The findings indicate that destination image construction on Xiaohongshu emerges through the interaction between visually driven attraction and text-based verification, where aesthetic representation stimulates initial interest while experiential narratives reinforce credibility and trust. Push motivations such as risk mitigation, authenticity seeking, and personalized travel preferences are digitally mediated through algorithmic exposure and peer validation, while pull factors extend beyond destination attributes to include platform-specific affordances such as recommendation precision and credibility through balanced user reviews. The study concludes that Xiaohongshu functions not merely as a promotional channel but as a digital infrastructure that shapes perception, reduces uncertainty, and influences tourism mobility patterns. These findings provide theoretical refinement of push–pull motivation in platform-mediated environments and offer strategic guidance for destination stakeholders in aligning digital representation with evolving Gen Z travel behavior